An Analysis of Teacher’s Strategies in Teaching Speaking - Donny Adiatmana Ginting; Yusrah; Damayanti (LPPM STKIP AL MAKSUM, 2020)
Speaking plays an important role in communication. This study is aimed at analysing teacher’s strategies in teaching speaking skill at SMP Negeri 2 Binjai. This study is conducted to show the types of teaching strategies in teaching speaking, the problems and solutions were faced by the teacher in learning process. This study is a qualitative study. The subject of the study is the teacher at SMP Negeri 2 Binjai. Interview was used in this study to collect the data. The technique of data analysis was interactive model analysis that is adopted from Yin, those are: compiling, disassembling, reassembling, interpreting, and concluding. The result showed that question and answer strategy was the only technique used by the teacher in teaching speaking. Its became the appropriate strategy due to the number of students in the classroom and the limited time in English learning. The problem faced by teacher in teaching speaking was a huge number of students in a class made him hard to control their speaking ability. Then, as a foreign language in Indonesia English becomes hard to learn by the EFL learner due to the lack of vocabulary. The solution of the problems is giving more English practice to the English learners and create students in group discussion. Keywords: Teacher’s Strategies, Speaking.